Metadata Harvesting:Tools and Services in India - Hirwade, M. A.; Bherwani, M. T. (Journal of Information and Knowledge, 2013)
Technological developments in Information Science have led to the emergence of new service paradigms. The creation of Open Access digital repository is a recent trend, which is progressing towards a stronger national information channel infrastructure. Alternatively, deluge of digital data and the rate at which the repositories of information are increasing are not affable because one needs to trace these individually. In order to facilitate interoperability, the role of Metadata Harvesting Service Providers is a crucial one. With this background the author has tried to study 8 major Metadata Harvesting Service Providers from India. It also focuses on interoperability of these digital repositories and the role of Metadata harvesting service providers in facilitating one stop shop and easy access to galore of resources contained in these repositories, thereby enhancing access to scholarly communications.